THE METHODOLOGY OF TRANSLATION OF DOCUMENTS FROM A FOREIGN LANGUAGE (International relations and international law Journal, 2016)
In this article the main methods of translation are considered. Author of this article try to demonstrate how an individualistic factor impact on the style and quality of translator`s job.
Keywords: document; translation methods